2006
DOI: 10.1038/sj.mp.4001924
|View full text |Cite
|
Sign up to set email alerts
|

Towards a muscarinic hypothesis of schizophrenia

Abstract: Although the neurotransmitter dopamine plays a prominent role in the pathogenesis and treatment of schizophrenia, the dopamine hypothesis of schizophrenia fails to explain all aspects of this disorder. It is increasingly evident that the pathology of schizophrenia also involves other neurotransmitter systems. Data from many streams of research including preclinical and clinical pharmacology, treatment studies, post-mortem studies and neuroimaging suggest an important role for the muscarinic cholinergic system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
215
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(219 citation statements)
references
References 188 publications
(190 reference statements)
3
215
0
1
Order By: Relevance
“…6). NDMC displays strong partial agonist activity at M 1 receptors (Davies et al 2005;Lameh et al 2007;Natesan et al 2007), and while CLZ has traditionally been considered to be a muscarinic antagonist, more recent work has shown that CLZ is a partial agonist at M 1 , M 2 , and M 3 receptors and is a full agonist at M 4 receptors (see Raedler et al 2007). Thus, CLZ and NDMC also appear to share similarities in terms of their activity at muscarinic receptors (which may or may not be related to their discriminative cue properties).…”
Section: Discussionmentioning
confidence: 99%
“…6). NDMC displays strong partial agonist activity at M 1 receptors (Davies et al 2005;Lameh et al 2007;Natesan et al 2007), and while CLZ has traditionally been considered to be a muscarinic antagonist, more recent work has shown that CLZ is a partial agonist at M 1 , M 2 , and M 3 receptors and is a full agonist at M 4 receptors (see Raedler et al 2007). Thus, CLZ and NDMC also appear to share similarities in terms of their activity at muscarinic receptors (which may or may not be related to their discriminative cue properties).…”
Section: Discussionmentioning
confidence: 99%
“…These and other findings suggest that this brain disorder arises from a genetic predisposition affecting neurodevelopmental processes, combined with exposure to environmental risk factors. 14 The complexity of the underlying physiological basis is highlighted by the multitude of pathways that have been implicated in pathogenesis including those involving dopaminergic, 15,16 serotonergic, 17,18 muscarinic [19][20][21][22] and glutamatergic signaling pathways. [23][24][25] It is, therefore, significant that PLC-b1 represents a point of convergence for these signaling pathways and that levels of the protein have been shown to be altered in the cortex of chronic schizophrenic patients, increasing in the prefrontal cortex and decreasing in the superior temporal gyrus.…”
Section: Introductionmentioning
confidence: 99%
“…Based on extensive evidence indicating the crucial role of the cortical cholinergic input system for attention Parikh et al, 2007;Sarter et al, 2006Sarter et al, , 2005a, the attentional symptoms of schizophrenia have been proposed to be mediated via abnormalities in the regulation and activity of this neuronal system Raedler et al, 2003Raedler et al, , 2007Sarter et al, 2005b). Recently, we demonstrated that in animals pretreated in accordance with an amphetamine (AMPH) regimen identical to the one used herein, the disruption of attentional performance triggered by AMPH challenges was a result, not just a correlate, of a prefrontal cholinergic input system that remained 'frozen' at baseline and failed to activate in response to the task onset .…”
Section: Introductionmentioning
confidence: 99%